2018
DOI: 10.1128/jvi.00093-18
|View full text |Cite
|
Sign up to set email alerts
|

TIM-1 Mediates Dystroglycan-Independent Entry of Lassa Virus

Abstract: Lassa virus (LASV) is an Old World arenavirus responsible for hundreds of thousands of infections in West Africa every year. LASV entry into a variety of cell types is mediated by interactions with glycosyltransferase LARGE-modified O-linked glycans present on the ubiquitous receptor α-dystroglycan (αDG). However, cells lacking αDG are permissive to LASV infection, suggesting that alternative receptors exist. Previous studies demonstrated that the phosphatidylserine (PtdSer)-binding receptors Axl and Tyro3 alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 78 publications
2
73
3
1
Order By: Relevance
“…Viral entry inhibitors are valuable as therapeutics, since blocking infection early in the life cycle will reduce cellular and tissue damage associated with the replication of incoming viruses and the production of viral progeny. LASV employs several key features in common with EBOV for its entry: (i) it is internalized into the endocytic pathway by a macropinocytotic-like process after initial contact with surface receptors/ attachment factors, (ii) low pH is needed to trigger fusion, and (iii) an endosomal, cholesterol binding receptor promotes endosomal escape (Lamp1 for LASV and NPC1 for EBOV) (12,(25)(26)(27)(28)(29)(30)(31)(32). Hence, for this study, we selected eight low-molecular-weight drugs shown to inhibit EBOV entry and directly compared their inhibitory activities against LASV and EBOV.…”
mentioning
confidence: 99%
“…Viral entry inhibitors are valuable as therapeutics, since blocking infection early in the life cycle will reduce cellular and tissue damage associated with the replication of incoming viruses and the production of viral progeny. LASV employs several key features in common with EBOV for its entry: (i) it is internalized into the endocytic pathway by a macropinocytotic-like process after initial contact with surface receptors/ attachment factors, (ii) low pH is needed to trigger fusion, and (iii) an endosomal, cholesterol binding receptor promotes endosomal escape (Lamp1 for LASV and NPC1 for EBOV) (12,(25)(26)(27)(28)(29)(30)(31)(32). Hence, for this study, we selected eight low-molecular-weight drugs shown to inhibit EBOV entry and directly compared their inhibitory activities against LASV and EBOV.…”
mentioning
confidence: 99%
“…The conserved and widely expressed receptor for extracellular matrix proteins, α-dystroglycan (α-DG), is a main receptor for Old World (OW) mammarenaviruses, such as lymphocytic choriomeningitis virus (LCMV) and Lassa virus (LASV) [38]. Secondary alternative receptors, including members of the Tyro3/Axl/Mer and T-cell immunoglobulin mucin (TIM) receptor families may account for LASV and LCMV infection of cells lacking fully glycosylated α-DG [44,45]. Cell entry of the OW hemorrhagic fever (HF) mammarenavirus Lujo virus (LUJV) is mediated by neuropilin (NRP)-2, a cell-surface receptor for semaphorins [46].…”
mentioning
confidence: 99%
“…In the past years, VSV-derived pseudoviruses were used in multiple studies to evaluate entry factors for hantaviruses, filoviruses and arenavirus among others. The studies demonstrated a very close correlation of pseudovirions with the pathogenic viruses (Kondratowicz, Lennemann et al 2011, Jemielity, Wang et al 2013, Moller-Tank, Kondratowicz et al 2013, Moller-Tank and Maury 2014, Kuroda, Fujikura et al 2015, Riblett, Blomen et al 2016, Brouillette, Phillips et al 2018, Jangra, Herbert et al 2018). Entry of HTNV and ANDV into A549 lung epithelial cells was significantly reduced in presence of anti-hTIM-1 blocking antibody (Fig.…”
Section: Discussionmentioning
confidence: 95%